"The ripples are big": Storying the impact of doping in sport beyond the sanctioned athlete. (May 2016) - Erickson, Kelsey; Backhouse, Susan H.; Carless, David
Abstract: Objective: The purpose of this paper was to extend current doping research efforts by shifting the focus away from a doping-user perspective to examine the experiences of elite athletes that have been personally affected by other athletes' doping behaviours. Design: This research works within the interpretive paradigm, adopting relativist ontology and transactional/subjectivist epistemology. Method: Conversational interviews were conducted with 'competitive' (N = 2) and 'retired' (N = 2) elite Track and Field athletes from multiple countries. In order to communicate the findings in a way that captures the complexity of the issue, whilst also appealing to the athletes this issue affects, creative non-fiction stories were used to present the findings. Results: Two stories were created; one incorporating the 'competitive' athletes' experiences and one presenting the 'retired' athletes' accounts. The stories detail financial, emotional, and relational implications stemming from others' use of performance enhancing drugs. Critically, the impact is not ephemeral; the retired athletes detailed the long-term implications of their experiences. Meanwhile, the competitive athletes suggest that given the current state of sport, they regularly have to defend their status as 'clean athletes'. Thus, the ripples of doping in sport appear to be far reaching and enduring. Conclusions: Incorporating a novel mode of knowledge production within the doping literature, the stories presented here demonstrate elite athletes' candid accounts of being impacted by others' doping behaviours in sport. This study also emphasises the value of adopting novel and creative approaches to data collection and representation within the field of doping research. Highlights: This study offers an alternative narrative and perspective on doping in sport. Creative non-fiction stories depict the complexity of elite athletes' experiences. Financial, emotional and relational implications stem from others doping in sport. Doping creates ripples that are far reaching and enduring, but rarely acknowledged.